PERFORMANCE ANALYSIS OF TUGU PANCASILA ROUNDABOUT IN PUTUSSIBAU CITY KAPUAS HULU DISTRICT - Darmawan, Hifzhan Hanif; Mukti, Elsa Tri; Kadarini, S. Nurlaily (Jurnal Teknik Sipil, 2024)
Tugu Pancasila Roundabout in Putussibau City is a 5-arm roundabout that organizes traffic in 5 directions of movement. Poor traffic management at this roundabout, such as the lack of roundabout signs and no separation island or median on roads other than the main road, makes motorists who should pass through the roundabout instead choose not to cross the roundabout and go against the flow because they want to reach their destination faster. In addition, due to the increasing population and the volume of vehicles traveling, it is anticipated that in the future, the Tugu Pancasila roundabout will have increasingly heavy traffic flows. The performance analysis of Tugu Pancasila Roundabout was calculated using MKJI 1997 and VISSIM software. The performance analysis of Tugu Pancasila Roundabout was carried out by taking roundabout geometric data, manually taking side obstacle data, and traffic volume data for three days using survey aids in the form of CCTV starting at 06.00 - 18.00 WIB. Analysis of the existing conditions in 2023, the highest degree of saturation is 0.62 with the level of service B; in the 2028 projection conditions, the highest degree of saturation is 0.73 with the level of service B; and in the 2033 projection conditions, the highest degree of saturation is 0.86 with the level of service E. With a poor level of service, the volume of vehicles and the roundabout capacity could be more balanced, so improvements are needed for the Tugu Pancasila Roundabout in Putussibau City. The improvement solution is to re-plan the roundabout following the Roundabout Planning Guidelines for Intersections (2004). For the results of the MKJI 1997 analysis of the roundabout re-planning solution, the 2028 projection obtained the highest degree of saturation of 0.54 with level of service B, and in the 2033 projection obtained the highest degree of saturation of 0.63 with level of service B. for the results of the VISSIM software simulation, the roundabout re-planning solution for the 2028 projection obtained a delay of 13.14 seconds with level of service B, and the 2033 projection obtained a delay of 15.60 seconds with level of service C.